The impact of credit risk on banking profitability in the UK - Miao, Jingyi (2020)
Credit risk is an extremely critical risk that commercial banks focus on and manage. The purpose of this paper is to explore influence of credit risk on profitability of commercial banks in the UK. The article selects NPLGL and LLPGL to measure credit risk. Also, ROAA, ROAE and NIM are employed as indicators of profitability. Meanwhile, in order to predict the results more accurately, other bank-specific variables as well as macroeconomic variables are chosen as control variables. Moreover, this paper applies the individual effects model and the SGMM model to explore the relationship between credit risk and profitability. It is found that credit risk faced by British commercial banks exerts a significantly negative impact on ROAA and ROAE, while it has a positive effect on NIM, and this effect is not significant. Concerning control variables, it should be noted that CTI is significantly and negatively related to profitability. Furthermore, capital adequacy is significantly and positively associated with ROAA. Additionally, understanding the extent of credit risk's influence on profitability enables commercial banks to adjust and improve credit risk management timely, making credit risk under the control of banks and improve profitability.